Effect of ethylenediamine on morphology of 2D Co-Mo-S@NG hybrids and their enhanced electrocatalytic activity for DSSCs application. (January 2020) - Ganesh, R. Sankar; Durgadevi, E.; Silambarasan, K.; Navaneethan, M.; Ponnusamy, S.; Kong, C.Y.; Muthamizhchelvan, C.; Shimura, Y.; Hayakawa, Y.
Abstract: Novel 2D Co-Mo-S anchored on nitrogen-doped graphene (NG) nanosheets was synthesized by simple and cost effective one step hydrothermal method. The effect of ethylenediamine (ETA) on morphology and catalytic activity of Co-Mo-S@NG was studied. Transmission electron microscopy image showed that morphology of Co-Mo-S nanorods and nanosheets changed into flower-like nanostructures composed of numerous sheets by ETA. Scanning transmission microscope showed the formation of Co-Mo-S nanoflower on the surface of NG. X-ray photoelectron spectra analysis confirmed the effective doping of nitrogen in graphene and Co-Mo-S. Counter electrode of dye sensitized solar cell was fabricated by simple spray pyrolysis method at 150 °C. Co-Mo-S@NG with ETA showed lower value of separation between anodic peak and cathodic peak (Epp), higher stability and higher current density compared with pure Cu-Mo-S@NG counter electrodes (CE). Co-Mo-S@NG with ETA showed 1.12% efficiency and current value (Jsc) of 7.22 ± 0.5 mA.